Supplementary files to Oogenesis and lipid metabolism in the deep-sea sponge Phakellia ventilabrum: a histological, lipidomic and transcriptomic approach, Manuscript IV, Thesis - Koutsouveli, Vasiliki (Uppsala University, 2020)
In this study, we used histology, lipidome profiling (UHPLC-MS), and transcriptomic analysis (RNA-seq) on the deep-sea sponge Phakellia ventilabrum (Demospongiae, Bubarida), a key species of North-Atlantic sponge grounds, with the goal to (i) assess the reproductive strategy and seasonality of this species, (ii) examine the relative changes in the lipidome signal and the gene expression patterns of the enzymes participating in lipid metabolism during oogenesis.

The dataset was originally published in DiVA and moved to SND in 2024.

In this study, we used histology, lipidome profiling (UHPLC-MS), and transcriptomic analysis (RNA-seq) on the deep-sea sponge Phakellia ventilabrum (Demospongiae, Bubarida), a key species of North-Atlantic sponge grounds, with the goal to (i) assess the reproductive strategy and seasonality of this species, (ii) examine the relative changes in the lipidome signal and the gene expression patterns of the enzymes participating in lipid metabolism during oogenesis.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Supplementary files to Oogenesis and lipid metabolism in the deep-sea sponge Phakellia ventilabrum: a histological, lipidomic and transcriptomic approach, Manuscript IV, Thesis
Keywords: natural sciences; naturvetenskaper; Natural Sciences; Naturvetenskap; Pharmaceutical Sciences; Farmaceutiska vetenskaper